Evolutionary Insights into the Length Variation of DNA Damage Response Proteins Across Eukaryotes - Wiredu-Boakye, Dominic; Higgins, Laurence; Gahura, Ondřej; Butenko, Anzhelika; Leonard, Guy; Freeman, Mark A; Kristmundsson, Árni; Moore, Karen; Harrison, Jamie W; Mac Donald, Shani; Yurchenko, Vyacheslav; Williams, Bryony A P; et al. (Genome biology and evolution, 2025)
Across the tree of life, DNA damage response (DDR) proteins play a pivotal, yet dichotomous role in organismal development and evolution. Here, we present a comprehensive analysis of 432 DDR proteins encoded by 68 genomes, including that of Nucleospora cyclopteri, an intranuclear microsporidia sequenced in this study. We compared the DDR proteins encoded by these genomes to those of humans to uncover the DNA repair-ome across phylogenetically distant eukaryotes. We also performed further analyses to understand if organismal complexity and lifestyle play a role in the evolution of DDR protein length and conserved domain architecture. We observed that the genomes of extreme parasites such as Paramicrocytos, Giardia, Spironucleus, and certain microsporidian lineages encode the smallest eukaryotic repertoire of DDR proteins and that pathways involved in modulation of nucleotide pools and nucleotide excision repair are the most preserved DDR pathways in the eukaryotic genomes analysed here. We found that DDR and DNA repair proteins are consistently longer than housekeeping and metabolic proteins. This is likely due to the higher number of physical protein-protein interactions which DDR proteins are involved. We find that although DNA repair proteins are generally longer than housekeeping proteins, their functional domains occupy a relatively smaller footprint. Notably, this pattern holds true across diverse organisms and shows no dependence on either lifestyle or mitochondrial status. Finally, we observed that unicellular organisms harbour proteins that are tenfold longer than their human homologues, with the extra amino acids forming interdomain regions with a clearly novel albeit undetermined function.
Keywords: molekulární evoluce; poškození DNA; protein length; DNA Damage; DNA lesions; Microsporidia; Humans; DNA Repair; intracellular parasites; Eukaryota; oprava DNA; fylogeneze; Phylogeny; DNA damage signalling; genome compaction; lidé; Evolution, Molecular